g-Factor measurements of first 2(+) states of heavy Te isotopes based on nuclear spin deorientation for nuclei recoiling in vacuum - Danchev, M; Pavan, J; Stone, N; Stuchbery, A; Baktash, C; Beene, J; Benczer-Koller, N; Bingham, C; Dupak, J; Galindo-Uribarri, A; Gross, C; Kumbartzki, G; et al. (2005)
We demonstrate that the recoil-in-vacuum (RIV) method can be used to determine the g-factor of the Coulumb excited first 2(+) state of Te-132. This was possible owing to advantages provided by CLARION (ORNL clover multidetector array) and the segmented charged particle detector HyBall. Calibratory experiments were performed with Te-122,Te-126,Te-130 and a g-factor of Te-132 was deduced g = (+)0.35(5). (c) 2005 Published by Elsevier B.V.